Acute lymphoblastic leukemia in adults - Josep-Maria Ribera (MDPI AG, 2011)
Acute lymphoblastic leukemia (ALL) is the most frequent neoplastic disease in children, being a rare disease in adults. Many of the advances in pediatric ALL have been through modifications in the doses and schedules of available agents as opposed to the introduction of new compounds. In recent years some improvements in the outcome of ALL in adults have occurred. Application of pediatric regimens to young and middle-aged adults shows promise to improve outcome. Advances in the supportive care of patients undergoing allogeneic stem cell transplantation (SCT), the use of alternative sources of hematopoietic stem cells and the use of reduced-intensity conditioning regimens will expand the number of patients who can benefit from this therapeutic modality. The evaluation of minimal residual disease will further stratify risk classification and redefine the role of therapeutic modalities such as SCT or biologic agents. New drugs such as thyrosin kinase inhibitors or monoclonal antibodies have led to incremental improvements in outcome. Advances in the genetic and epigenetic mechanisms of the disease provide hope that targeted therapies can more effectively treat the disease with less toxicity.